Methods of evaluation of intangible assets and intellectual capital - Osinski, M.; Selig, P. M.; Matos, F.; Roman, D. J. (Journal of Intellectual Capital, 2017)
Purpose: The competitive model has changed. In this context, society entered into an era in which intangible assets are the greatest assets of a company. However, some gaps and uncertainties are presented in the literature as to understand the value of a company based on knowledge intensive activities. The purpose of this paper is to analyze the methods of evaluation of intangible assets in the context of business, economic and strategic management. Design/methodology/approach: This is a qualitative research. This research is characterized as descriptive, bibliographic, inductive. Findings: The main results of this research can highlight the existence of valuation methods of intangible assets intended for specific industries, as public and/or private, that can be better aligned to the context of business; economic and/or strategic management. Originality/value: It was found that intangible assets are a current topic and increasingly addressed in the literature.